Urgensi dan Tujuan Studi Islam Dalam Metodologi Studi Islam - Ahmad Supandi; Siti Ainul Hayat; Maftuh Ajmain (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This study aims to explain the meaning of Islamic studies conceptually and terminologically, identify the scope and fields of study within Islamic studies, analyze the urgency of Islamic studies in personal, social, and academic life, explain the main objectives of Islamic studies in forming a comprehensive understanding and practice of Islamic teachings, and understand the role of Islamic studies in facing the dynamics and challenges of globalization. The method used is library research with a descriptive-analytical approach to literature related to Islamic studies. The results show that Islamic studies is a scientific discipline that comprehensively and systematically examines the teachings, sources, history, thought, and practices of Muslim life. The scope of Islamic studies is very broad, covering the Qur'an, hadith, creed (aqidah), jurisprudence (fiqh), Sufism, philosophy, history, and contemporary issues. The urgency of Islamic studies lies in its ability to guide individuals and societies toward a meaningful and civilized life, while wisely and scientifically addressing the dynamics of modern challenges such as globalization, the digital revolution, and social change.